Contribution of Communicative Stages in the Argument-Driven Inquiry Model to Enhance Students' Scientific Argumentation Skills - Dewannia Fariska Herman; Endang Susantini; Tarzan Purnomo; Anas Wasa (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2026)
This study investigates the effectiveness of the Argument-Driven Inquiry model assisted by worksheets in improving students' scientific argumentation skills in physics learning. Using an explanatory sequential mixed-methods design, this study involved 31 eighth-grade students at MTs Negeri 1 Jember who studied the topics of vibrations, waves, and light. Quantitative data were collected through pretest and posttest assessments, with argument quality measured using the Toulmin Argumentation Pattern (TAP) framework. The results showed a statistically significant improvement in students' scientific argumentation skills (t = -26.1, p <0.001, Cohen's d = 4.69), indicating a very large effect size. Qualitative findings indicate that the six stages of ADI cumulatively contribute to the development of the five components of argumentation (claim, evidence, warrant, support, and counterargument). The argumentation sessions and peer review stage are particularly important in enabling students to develop support and counterarguments through dialogic interaction and critical evaluation. This study confirms that the ADI model, supported by structured worksheets, can create a repetitive learning environment where arguments are continuously constructed, tested, critiqued, and refined, thereby facilitating students' progress toward higher levels of scientific argumentation.